2011
DOI: 10.1371/journal.ppat.1001261
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Plant Surface Signals are Sensed by Different Mechanisms in the Rice Blast Fungus for Appressorium Formation

Abstract: Surface recognition and penetration are among the most critical plant infection processes in foliar pathogens. In Magnaporthe oryzae, the Pmk1 MAP kinase regulates appressorium formation and penetration. Its orthologs also are known to be required for various plant infection processes in other phytopathogenic fungi. Although a number of upstream components of this important pathway have been characterized, the upstream sensors for surface signals have not been well characterized. Pmk1 is orthologous to Kss1 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
230
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 203 publications
(238 citation statements)
references
References 54 publications
7
230
0
1
Order By: Relevance
“…Many questions regarding fungal MAPK signaling remain unanswered, and upcoming studies should, for instance, focus on the understanding of upstream mechanisms leading to MAPK activation. Recently, homologs of the yeast osmosensors Sho1 and Msb2 (Figure 1) have been shown to act upstream of pathogenesis-related MAPK cascades in U. maydis ( Figure 5; Lanver et al, 2010), M. oryzae (Figure 6; Liu et al, 2011), and F. oxysporum (Pérez-Nadales and Di Pietro, 2011). Along with the previously identified G protein-coupled receptor Pth11 from M. oryzae (Figure 6; DeZwaan et al, 1999;Kulkarni et al, 2003), these candidate receptors likely ensure MAPK cascade activation following recognition of specific ligands.…”
Section: Upcoming Challenges and Concluding Remarksmentioning
confidence: 99%
“…Many questions regarding fungal MAPK signaling remain unanswered, and upcoming studies should, for instance, focus on the understanding of upstream mechanisms leading to MAPK activation. Recently, homologs of the yeast osmosensors Sho1 and Msb2 (Figure 1) have been shown to act upstream of pathogenesis-related MAPK cascades in U. maydis ( Figure 5; Lanver et al, 2010), M. oryzae (Figure 6; Liu et al, 2011), and F. oxysporum (Pérez-Nadales and Di Pietro, 2011). Along with the previously identified G protein-coupled receptor Pth11 from M. oryzae (Figure 6; DeZwaan et al, 1999;Kulkarni et al, 2003), these candidate receptors likely ensure MAPK cascade activation following recognition of specific ligands.…”
Section: Upcoming Challenges and Concluding Remarksmentioning
confidence: 99%
“…In the gray mold Botrytis cinerea, the homologous signaling module is essential for the differentiation of sclerotia and contributes to the control of microconidiation (17). In various plant-parasitic fungi, MAP kinases are pathogenicity factors and are involved in plant surface recognition and the differentiation of infection structures, such as appressoria (18)(19)(20)(21).…”
mentioning
confidence: 99%
“…The detail mechanisms underlying specificity of Msb2-mediated cutin monomer and surface hydrophobicity sensing, as well as the exact role of Sho1 in leaf wax sensing, are still unknown. It was, however, suggested that these proteins might play overlapping role in sensing appressorium inducing signals (Liu et al 2011). Surprisingly, targeted gene deletion of M. oryzae MoMSB 2 and MoSHO 2 did not significantly alter the progression of appressorium differentiation on host surface (Liu et al 2011) From these observations, the likely existence of yet to be identified proteins in the rice blast fungus with an overlapping role in mediating appressorium morphogenesis was speculated.…”
Section: The Role Of Cutin and Cuticular Wax In Appressorium Morphogementioning
confidence: 99%
“…It was, however, suggested that these proteins might play overlapping role in sensing appressorium inducing signals (Liu et al 2011). Surprisingly, targeted gene deletion of M. oryzae MoMSB 2 and MoSHO 2 did not significantly alter the progression of appressorium differentiation on host surface (Liu et al 2011) From these observations, the likely existence of yet to be identified proteins in the rice blast fungus with an overlapping role in mediating appressorium morphogenesis was speculated. This hypothesis was confirmed recently after the CFEM (conserved fungal-specific extracellular membrane spanning) domain of PTH11 like GPCR (G-protein coupled receptors) was identified and characterised in M. oryzae .…”
Section: The Role Of Cutin and Cuticular Wax In Appressorium Morphogementioning
confidence: 99%
See 1 more Smart Citation